2014
DOI: 10.4236/ajps.2014.518299
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nutrition <i>vis-à-vis</i> Aconitase Activity and Ferritin Accumulation in Tropical <i>Indica</i> Rice Cultivars Differing in Grain Iron Concentration

Abstract: Effect of Fe nutrition on Fe acquisition, aconitase enzyme activity and assimilation of the element in ferritin protein was studied in two indica rice cultivars viz. Sharbati and Lalat having contrasting grain Fe concentration. Young rice seedlings were grown in hydroponics with different levels of Fe. For comparison, the two cultivars were also grown in the field under natural conditions of rice culture. Iron accumulation, aconitase activity and ferritin level were higher in the high Fe containing cultivar, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This decreased Ni bioavailability in soil solution has led to enhanced uptake of Fe by rice plant and later its accumulation in grains. Our findings are in line with Panda et al (2014) who found that application of Fe supplementation in the growing medium increased Fe accumulation, which in turn increased aconitase activity, and ferritin accumulation in the seedlings of two rice cultivars.…”
Section: Discussionsupporting
confidence: 93%
“…This decreased Ni bioavailability in soil solution has led to enhanced uptake of Fe by rice plant and later its accumulation in grains. Our findings are in line with Panda et al (2014) who found that application of Fe supplementation in the growing medium increased Fe accumulation, which in turn increased aconitase activity, and ferritin accumulation in the seedlings of two rice cultivars.…”
Section: Discussionsupporting
confidence: 93%
“…When both susceptible and tolerant cultivars, BR-IRGA 409 and EPAGRI 108 respectively, were subjected to high concentrations of Fe there was less accumulation of this element and greater accumulation of ferritin in the tolerant cultivar, suggesting that this protein may be involved in this mechanism of tolerance ( Silveira et al ., 2009 ). However, a study by Panda et al . (2014) found that when there is Fe accumulation, the activity of aconitase and ferritin levels are higher in a cultivar that accumulates higher concentrations of Fe compared to the cultivar that has a lower concentration of this element.…”
Section: Quantitative Trait Locimentioning
confidence: 97%
“…Aconitase (ACO) requires many Fe-S groups because Fe-S is unstable in ACO, so it must be replaced many times by other Fe-S groups. The result of isocitrate changes in the Krebs cycle is alpha-ketoglutarate which after being reacted with the amino acid glutamate (glutamic dehydrogenase or oxaloacetate-glutamate transaminase) will become glutamic acid which is the raw material for making chlorophyll (Lushchak et al, 2014;Panda et al, 2014;Rout & Sahoo, 2015).…”
Section: Introductionmentioning
confidence: 99%